Art and dance in dialogue body, space, object - Whatley, Sarah; Racz, Imogen; Paramana, Katerina; Crawley, Marie-Louise (Cham, Switzerland Palgrave Macmillan, 2020)
This interdisciplinary book brings together essays that consider how the body enacts social and cultural rituals in relation to objects, spaces, and the everyday, and how these are questioned, explored, and problematised through, and translated into dance, art, and performance. The chapters are written by significant artists and scholars and consider practices from various locations, including Central and Western Europe, Mexico, and the United States. The authors build on dialogues between, for example, philosophy and museum studies, and memory studies and post-humanism, and engage with a wide range of theory from phenomenology to relational aesthetics to New Materialism. Thus this book represents a unique collection that together considers the continuum between everyday and cultural life, and how rituals and memories are inscribed onto our being. It will be of interest to scholars and practitioners, students and teachers, and particularly those who are curious about the intersections between arts disciplines
Includes bibliographical references and index.
Keywords: Human figure in art; Art and dance